2018
DOI: 10.3389/fneur.2018.00221
|View full text |Cite
|
Sign up to set email alerts
|

Compromised Blood–Brain Barrier Integrity Is Associated With Total Magnetic Resonance Imaging Burden of Cerebral Small Vessel Disease

Abstract: ObjectiveSeveral studies have demonstrated that compromised blood–brain barrier (BBB) integrity may play a pivotal role in the pathogenesis of individual cerebral small vessel disease (cSVD) markers, but the association between BBB permeability and total magnetic resonance imaging (MRI) cSVD burden remains unclear. This study aimed to investigate the relationship between BBB permeability and total MRI cSVD burden.MethodsConsecutive participants without symptomatic stroke history presented for physical examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 32 publications
1
40
0
Order By: Relevance
“…This matter of fact most likely depends on the severity of the SVD (2, 9-11) and the exact disease stage (9,10,12,(40)(41)(42). WMH may present with impaired blood brain barrier, loss of oligodendrocytes and reduced density of glia, vacuolation and axonal damage and impaired white matter integrity as reported on diffusion tensor imaging (2,9,10,12,(43)(44)(45). However, as in MSL, conventional MRI does not allow for a differentiation of histologically different WMH (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…This matter of fact most likely depends on the severity of the SVD (2, 9-11) and the exact disease stage (9,10,12,(40)(41)(42). WMH may present with impaired blood brain barrier, loss of oligodendrocytes and reduced density of glia, vacuolation and axonal damage and impaired white matter integrity as reported on diffusion tensor imaging (2,9,10,12,(43)(44)(45). However, as in MSL, conventional MRI does not allow for a differentiation of histologically different WMH (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…The total CSVD score and most of the individual imaging markers of CSVD were associated with the aortic pulse wave velocity (PWV) (Del Brutto et al, 2019). A study revealed that BBB permeability in the brain measured by dynamic contrast enhancement (DCE)-MRI was positively correlated with total CSVD burden (Li et al, 2018). Higher total CSVD burden in the brain was associated with lower plasma volume fraction (Li et al, 2018), and blood plasma volume was related to the cerebral blood flow (CBF) (Arba et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A study revealed that BBB permeability in the brain measured by dynamic contrast enhancement (DCE)-MRI was positively correlated with total CSVD burden (Li et al, 2018). Higher total CSVD burden in the brain was associated with lower plasma volume fraction (Li et al, 2018), and blood plasma volume was related to the cerebral blood flow (CBF) (Arba et al, 2017). However, the relationship between global CBF and total CSVD score is uncertain until now.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, higher load of WMH is associated with adverse age-associated cognitive outcomes, such as slowed processing speed and increased risk of AD dementia 40,41 . In the absence of frank neurodegenerative phenotypes, age-associated WMH is frequently presumed secondary to cerebral vascular endotheliopathies resulting in increased BBB leakage and activation of CNS immune system, leading to reactive gliosis 40,[42][43][44][45] . In this model, endothelial cells play a central role.…”
Section: Discussionmentioning
confidence: 99%